Chinese Indonesians after May 1998 How they fit in the big picture - Anggraeni, Dewi (UI Scholars Hub, 2017)
For Chinese Indonesians, May 1998 is a significant historical marker, twelfth and thirteenth being two concentrated days of riots and atrocities in Jakarta, followed by more, albeit on smaller scales, in Solo, Surabaya, and a number of other cities. Destruction of properties belonging to them, and rapes of their women, occurred. Then Indonesia witnessed the end of Suharto's rule when the president resigned on 21 May 1998. A gradual political turn-around followed; Chinese Indonesians found room to move. The subsequent governments revoked restrictive regulations put in place by the New Order government, and lifted the suppression on cultural expression by Chinese Indonesians. The situation has progressed in conjunction with China's rise in global economic dominance. Does China's increasing international profile and rising global economic dominance help Chinese Indonesians? This article seeks to find some answer to the question as it looks at the development in the big picture; how and to what extent the social perceptions of Chinese Indonesians have evolved among the mainstream population; how they perceive themselves and believe how others perceive them; and how these may influence their lives as Indonesian citizens.